Investigating the potential of EDA data from biometric wearables to inform inclusive design of the built environment. (November 2022) - Willis, Katharine S.; Cross, Elizabeth
Abstract: This paper presents a pilot of a method which measures quantitative biometric data to understand the emotional response of people to their physical environment. The aim of the audit method is to address the problem of lack of accessibility of public buildings for those with hidden disabilities. People with invisible disabilities such as Autistic Spectrum Disorders (ASD, Autism) sometimes feeling forced to withdraw from public spaces and communities and unfamiliar or busy environments such as art galleries can be particularly problematic (Amaze, 2018). As part of the Audit, data is collected using a wearable biometric device that is mapped against internal location. In this study the EDA (Electrodermal Activity) Audit was trialed with participants with ASD at a public art gallery in UK. The results reveal that participants with ASD experienced a greater increase in stress level compared to the neurotypical control participants. Areas where noticeable 'peaks' of stress were recorded usually had a restricted view or required human interaction. Comparison of GSR (Galvanic Skin Response) data with questionnaire information gathered before and after visiting the gallery also implies that the participants with ASD were less able to articulate their emotional response to spaces. We discuss the development of an EDA Audit method that could provide knowledge to help designers envision spaces that are more inclusive. Highlights: This paper presents a methodology for auditing the emotional responses of people to the bult environment. An EDA Data Audit is a method to evaluate the features of buildings that can be barriers to participation of people with hidden disabilities such as ASD. Findings indicate that people with ASD experience a significant emotional response (that correlates to stress) to the environmental features. We suggest that the EDA Audit method could contribute to decisions about what is built; a step towards inclusive design.